Peningkatan Kualitas Sumber Daya Manusia di Lembaga Pendidikan Tajaul Karomah Desa Situ Gadung Kabupaten Tangerang - Ismanto, Budi; Jaenudin, Jaenudin; Putri, Aldila Rahma (Jurnal PKM Manajemen Bisnis, 2025)
Human resource quality is a key factor in achieving excellence in educational institutions. Many schools, particularly in developing or rural areas, face challenges in improving the skills and professionalism of their staff and organizational management. In response, a community service activity (PKM) titled "Improving the Quality of Human Resources at Tajaul Karomah Educational Institution, Situ Gadung Village, Tangerang Regency" was conducted to address these needs. The primary objective of this PKM was to strengthen the competence of teachers, school staff, foundation administrators, and student leaders in school governance, communication, and teamwork. The activity took place at Tajaul Karomah School on April 16, 2025. It was carried out by 12 lecturers from Universitas Pamulang and attended by 23 participants comprising teachers, staff, and foundation administrators, along with 10 student council (OSIS) members. The implementation methods included material presentations, simulations, discussions, and Q&A sessions, designed to create interactive and practical learning experiences. These approaches encouraged active participation and real-time problem-solving. As a result, the participants reported increased understanding of effective school leadership, improved communication strategies, and enhanced collaboration skills. The activity also fostered closer ties between higher education institutions and community-based schools, supporting sustainable educational development.